Estimation of development level of technical skills of orienteering athletes - Shyp Nadiya (Kharkiv State Academy of Physical Culture, 2019)
Purpose: study of the problem of assessing the level of technical training of the orienteering athletes, the development, implementation of practical tests that could possibly help the coach and athletes to identify prospects for further improvement, eliminate the shortcomings in technical training. In particular, such an element of technology as map reading was studied. Material and methods: analysis of the level of training of the students of the pedagogical university engaged in the section of sports orienteering was carried out. Literary sources were also studied and technical training tests were developed on the basis of this material. After applying the test system, an analysis of student performance was compared with the control group. Result: we were able to observe that the systematic use of tests has greatly improved the level of technical training of athletes and can be recommended for use in the training process. Conclusions: given the variety of competitive activities in sports orienteering, the large number and creative use of tests, the individualization of them will help athletes to reach their full potential.